Ink-gel simultaneous embedded 3D printing - Van Driel, Adrian (Department of Mechanical Engineering, 2025)
3D printing has improved by leaps and bounds. The gains include both the hardware and software. With 3D printers increasingly becoming staples of many a laboratory and engineering workshop, naturally comes the application of 3D printing to ever more significant issues. Some of these new applications encouraged the use of 3D printing to solve problems involving printing materials that do not solidify in the near-instantaneous manner that most existing methodologies used in 3D printing require. The material requirements of liquid or gel materials that may take minutes or even hours to solidify prompted the invention of embedded 3D printing. Embedded 3D printing is a methodology whereby a liquid is 3D printed into a support gel that supports the printed material's form until it can cure. This project aims to design and test a prototype that may increase the useful print volume of an embedded 3D printer modified from an existing low-cost fused deposition modelling type 3D printer. To create parts using embedded 3D printing in the past, a support bath needed to be prepared before printing and the printed material nozzle needed to be longer than the shortest axis of the part. With that design, the requirement for a long nozzle to print larger parts introduces some problems. More extended nozzles require more pressure to extrude material, are more likely to clog than shorter nozzles, create more of a disturbance in the support gel and are more susceptible to deflection over the nozzle's length. A need was identified to print support gel on demand and, in that way, make an embedded printer that could expand the useful print volume without increasing the length of the nozzle. Various sub-assemblies were designed, tested, and iteratively improved until the entire assembly could be tested together to achieve simultaneous printing of the printed material and the support gel. This assembly would be called the Dual Ink-Gel Extruder (DIGEX). The printed material and the support gel were mixed in the same lab as the 3D printer, and the rheological properties of several concentrations of the support gel were tested and analysed to best enable simultaneous printing. Printed material and gel deposition methodologies were developed for this purpose, and their performance was analysed for best results. Several iterations of the electrical hardware, the software, and the slicer configurations were tested and iterated for use with DIGEX. These improvements culminated in a result that could successfully demonstrate the concept of simultaneous dual extrusion. However, some new complications were introduced in the printing process that need further iterations and research to enable large-format embedded 3D printers